Influence of Cultivars‚ Calcium Chloride and Periods on Fruit Storage Behavior of Pomegranate (Punica granatum L.) - Al-Bamarny, Sarfaraz Fatah Ali; Yonis, Azad Hassan (Sulaimani Journal for Pure and Applied Sciences, 2015)
Fruits of two local pomegranate cultivars (Sharmny and Hablary) were harvested during 2011 season; harvested fruits were dipped in 0, 2 and 4% CaCl2 for 4 minutes and stored at ambient temperature for four storage periods (1, 2, 3 and 4) months. Results revealed that Hablary cultivar was significantly maintained titratable acidity (%), reduced fruit weight loss and fruit decay compared to Sharmny cultivar. Moreover, Fruit dipped in 4 % CaCl2 had a significant decrease in fruit weight loss and recorded the highest TSS, TSS/TA ratio and vitamin C. compared to other treatments. Furthermore, TSS, TSS/TA ratio and fruit weight loss were significantly increased, while TA and vitamin C significantly reduced with the prolonging of storage periods.
Keywords: Pomegranate; Cultivars; Calcium chloride; Storage periods